Arung Bettempola La Tiringeng Tontaba' di Kerajaan Wajo Abad Ke-16: Dari Monarki Absolut Menjadi Monarki Konstitusional - Rika Liyana (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2017)
This study aims to determine the system of government in the Kingdom of Wajo before La Tiringeng To Taba’ into Arung Bettempola, the role of Arung Bettempola La Tiringeng To Taba', and the impact of Arung Bettempola La Tiringeng To Taba’ role on the development in the Kingdom of Wajo. The method used is descriptive qualitative research method using historical method, through the stages of work that includes heuristics, criticism, interpretation, and historiography. The results show La Tiringeng To Taba 'is one of the scholars who have contributed to the democratic government in the Kingdom of Wajo. The results of Arung Bettempola La Tiringeng To Taba’ thought the Wajo Constitution under the Lapa'deppa Agreement' in 1476 made the Kingdom of Wajo a State of law, which respects human rights and the sovereignty of the people. Based on the result of the research, it can be concluded that the role of Bungempola La Tiringeng To Taba’ in the Kingdom of Wajo has had an impact for the development of the Kingdom of Wajo, among others, namely the fundamental change in the system of government, from absolute monarchy to constitutional monarchy.